Outer space and cyberspace - Majsova, Natalija (Teorija in praksa, 2014)
The text examines the relationship between cyberspace and outer space. It starts off with a peculiar observation that outer space themed video games are abundant, while scholarly and expert literature about them is virtually non-existent. The text proceeds to examine the implications of invoking outer space into video games, as they might appear, if one first critically analyses the concept of outer space imagination. Then, it faces this analysis with video games, supposedly set in outer space, following the questions set out by the pioneers of the spatial turn in video games studies. This analysis allows the author to argue that video games set in outer space in fact have very little to do with the theoretical imagination of outer space, and that the latter may more fruitfully be sought in games set in so-called alternative worlds.
Keywords: Cyberspace; fantastika; Kibernetski prostor; Universe; Vesolje; Video games; Videoigre